PENGARUH HEDONIC DAN UTILITARIAN MOTIVE TERHADAP BRAND TRUST McDONALD’s MELALUI BRAND SATISFACTION - Gede Dimas Harikusuma; Lalu M. Furkan; Emilia Septiani (Fakultas Ekonomi dan Bisnis Universitas Mataram, 2022)
This study aims to determine the effect of hedonic and utilitarian motives on brand trust mediated by their satisfaction with McDonald's brand products. This research was conducted by distributing 100 questionnaires to respondents who had consumed McDonald's products. The analytical technique used is quantitative analysis technique with path analysis method using SEM AMOS. In this study, it was found that there was a positive and significant effect of hedonic and utilitarian motives on McDonald's brand trust through satisfaction with the brand.